Supporting the United Nation’s Sustainable Development Goals: A qualitative study on Chow Kit road marginalized group mini library makeover / Nurfarawahidah Badruesham, Hazlin Hasan and Muniratul Husna Mohamad Zaki - Badruesham, Nurfarawahidah; Hasan, Hazlin; Mohamad Zaki, Muniratul Husna (Universiti Teknologi MARA Cawangan Pahang, 2021)
With the main objectives to reach out to the children of Chow Kit, Kuala Lumpur and help them own a convenient mini library as a place for them to read and learn, a mini library makeover project was conducted by UiTM Cawangan Pahang’s Al-Bukhari Library Team. The project was also conducted to fulfil the United Nations (UN) Sustainable Development Goals (SDGs) agenda in terms of equitable quality of education (SDG4) and reduce inequality to information which are central to an individual’s independence (SDG10). Buku Jalanan Chow Kit (BJCK) and Sekolah Bimbingan Jalinan Kasih (SBJK) were selected for the project as they provided the space to learn for marginalized groups of children who do not have the privilege to attend school. This research employed qualitative methods with in-depth interviews with volunteers and teachers of these places based on how they operate the places, the benefits for the kids, volunteers and teachers and the impacts to their places after the makeover project conducted earlier. The findings concluded that to keep on attracting and sustaining the reading program for these marginalized children, the researchers could further assist the teachers and volunteers in developing a library with improved reading modules as well as the addition of ICT skills and collection management skills for these kids. Opportunity for future research involving other related SDGs agenda to these places has also been identified and expected to benefit these children more in the future.